Counseling and psychotherapy with children and adolescents : theory and practice for school and clinical settings - Prout, H. Thompson, 1947-; Fedewa, Alicia L. (New Jersey Wiley, 2015)
"A comprehensive, theory-based approach to working with young clients in both school and clinical settings. Counseling and Psychotherapy with Children and Adolescents, Fifth Edition provides mental health professionals and students with state-of-the-art theory and practical guidance for major contemporary psychotherapeutic schools of thought. Children and adolescents are not just small adults; they have their own needs, requirements, and desires, on top of the issues presented by still-developing brains and limited life perspective. Providing care for young clients requires a deep understanding of the interventions and approaches that work alongside growing brains, and the practical skill to change course to align with evolving personalities. The thoroughly revised fifth edition is a comprehensive reference, complete with expert insight.Organized around theory, this book covers both clinical and school settings in the fields of psychology, counseling, and social work. Coverage of the latest thinking and practice includes Cognitive Behavioral, Rational-Emotive, Reality Therapy, Solution Focused, Family Systems, and Play Therapy, providing a complete resource for any mental health expert who works with young people.Understand the major approaches to counseling and psychotherapeutic interventionsDiscover the ethical and legal implications of working with children and adolescentsLearn how to employ culturally responsive counseling with younger clientsExamine interventions for children and adolescents with disabilities and health care needsThis updated edition includes a stronger emphasis on the clinical application of theory to specific disorders of childhood and adolescence, and new coverage of the legal and ethical issues related to social media. Chapters include a case studies and online resources that make it ideal for classroom use, and new chapters on Solution-Focused Therapy and Play Therapy enhance usefulness to practicing therapists. Expert guidance covers techniques for working with individuals, groups, and parents, and explores the efficacy of the theories under discussion"--Provided by publisher.
Machine generated contents note: Table of ContentsChapter 1 Counseling and Psychotherapy with Children and Adolescents: Historical, Developmental, Integrative, and Effectiveness PerspectivesH. Thompson Prout and Alicia L. Fedewa Chapter 2 Ethical and Legal Issues in Psychological Interventions with Children and AdolescentsAlicia L. Fedewa, Susan M. Prout and H. Thompson ProutChapter 3 Culturally responsive Interpersonal Psychotherapy with children and adolescentsJanine Jones, PhDChapter 4 Play TherapySue BrattonChapter 5 Cognitive-Behavioral and Behavioral ApproachesRich Gilman and Kathleen ChardChapter 6 Rational Emotive Behavior TherapyRaymond DiGiuseppe and Oana Alexandra DavidChapter 7 Reality Therapy ApproachesGerald B. FullerChapter 8 Solution-Focused ApproachesJohn J. MurphyChapter 9 Systemic Approaches: Family TherapyWilliam B. Gunn Jr., Joni Haley, Anne M. Prouty and Janet RobertsonChapter 10 Children and Adolescents with Disabilities: Implications for InterventionsJonathan M. Campbell, Ph.D., Lisa A. Ruble, Ph.D., and Rachel K. Hammond, Ph.D.
Includes bibliographical references and index.
Keywords: Psychotherapy; Adolescent; Child; Counseling